Perceived Differentiation and Personalization Teaching Approaches in Inclusive Classrooms: Perspectives of Students and Teachers - Lindner, Katharina-Theresa; Alnahdi, Ghaleb H.; Wahl, Sebastian; Schwab, Susanne (Frontiers in Education, 2019)
As indicated by the Warnock Report, even forty years ago, the necessity of responding to different student abilities and needs in school and thus the importance of adequate adaption of a regular curriculum regarding differentiation and personalization had already been described. Due to changes in policy and legislative frameworks, more and more students with special educational needs (SEN) attend regular education. However, placing the students with SEN within mainstream classrooms does not automatically lead to changes in teaching practices in these classrooms. In line with this, it would be interesting to know the way in which and to what extent students in inclusive classes perceive established inclusive practices, such as differentiation and personalization. Therefore, data from 47 inclusive classes from North Rhine-Westphalia (Germany) were collected. In total, 872 primary school students (grade 4; ages 9–11 years) were asked to rate how frequently their class teachers used inclusive instructional practices (personalization and differentiation) using the Inclusive Classroom Practices Scale (ITPS). In addition to students, teachers were also asked to rate their own teaching practices in general and then in addition for each student separately. As differentiated instruction and multifaceted teaching practices are considered to be measures for meeting the needs of children with different educational needs, results that show a high use of these approaches were expected. Descriptive results indicate a consistent homogeneous understanding of prevailing inclusive teaching practices, which could be characterized by existing, but not intensive implementation, of inclusive practices. Differences regarding students’ gender, migrant background, or SEN were not found for the students’ ratings of teachers’ inclusive practices or the teachers’ self-ratings group. Moreover, the teachers’ student-specific ratings indicate that teachers did not strongly differentiate or personalize with a focus on students’ characteristics. A small overlap between teachers’ general ratings of their own inclusive teaching practices and students’ individual ratings was found. The results of the current study provide insights into actual inclusive teaching practices in German inclusive classrooms and make it possible to address the need for action and inclusive interventions.